Translation and validation of the PACIC+ questionnaire: the Thai version - Zeugfang, Daniel; Wensing, Michel; Szecsenyi, Joachim; Krug, Katja (BMC family practice, 2018)
The number of patients with chronic illness is increasing worldwide. These patients usually receive care from a primary care facility. The Patient Assessment of Chronic Illness Care (PACIC) is a tool that is increasingly used in several countries to measure how the patients perceive the care they receive. The goal of this validation study is to provide and validate an extended version of the tool, the PACIC+ questionnaire, in Thailand.